2010
DOI: 10.1063/1.3517810
|View full text |Cite
|
Sign up to set email alerts
|

On temperature-dependent experimental I-V and C-V data of Ni/n-GaN Schottky contacts

Abstract: We report the current-voltage (I-V) and capacitance-voltage characteristics (C-V) of Ni/n-GaN Schottky diodes. Gallium nitride is a highly promising wide band gap semiconductor for applications in high power electronic and optoelectronic devices which require Schottky barriers for modulating the channel mobile charge. The I-V and C-V characteristics of the diodes have been measured in the temperature range of 80–400 K with steps of 20 K. Thermal carrier concentration and barrier height versus temperature plots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 53 publications
7
43
1
Order By: Relevance
“…In our case, the nonideal behavior is probably due to the defects related to the as grown AlGaN semiconductor, such as residual structural defects and dislocations. They can yield a local reduction of the SBH and leads to inhomogeneities in the conduction transport [3,[24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…In our case, the nonideal behavior is probably due to the defects related to the as grown AlGaN semiconductor, such as residual structural defects and dislocations. They can yield a local reduction of the SBH and leads to inhomogeneities in the conduction transport [3,[24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…19 In addition to this, IF of 1.04 and higher SBH of 1.15 eV were calculated from I-V measurements for Cu/n-GaN, as compared to the values for Ni/n-GaN where IF and SBH were found to be 1.05 and 0.97 eV, respectively. From the previous reports on Ni/n-GaN Schottky barrier diodes, [13][14][15][16] it has been observed that in this metal/semiconductor diode, the SBH lied in between the values predicted by the Schottky-Mott model 20,21 (φ B = φ m − χ) and the Bardeen model 22 (φ B = (E g /q) − φ o ). Here, φ B is the SBH, φ m is the metal work function, χ is the electron affinity of the semiconductor, E g is the bandgap of the semiconductor, q is the electronic charge and φ o is the energy location of the charge neutrality level.…”
Section: Introductionmentioning
confidence: 99%
“…28 A similar deviation of the estimated values of Schottky junction parameters from theoretically predicted values is already reported by other researchers. 29,30 Surface states, interfacial defects, material non-uniformity, dislocation-related current paths, etc., are proposed to be linked with this kind of non-ideal behaviour of Schottky junction parameters. 16,29,31 In addition, a non-ideal behaviour modifies the ideality factor significantly.…”
Section: à2mentioning
confidence: 99%